Human Dystrophin Dp71ab Enhances the Proliferation of Myoblasts Across Species But Not Human Nonmyoblast Cells - Farea, Manal; Maeta, Kazuhiro; Nishio, Hisahide; Matsuo, Masafumi (Frontiers in Cell and Developmental Biology, 2022)
Dystrophin Dp71 is an isoform produced from the Dp71 promoter in intron 62 of the DMD gene, mutations in which cause Duchenne muscular dystrophy. Dp71 is involved in various cellular processes and comprises more than 10 isoforms produced by alternative splicing. Dp71ab, in which both exons 71 and 78 are deleted, has a hydrophobic C-terminus that is hydrophilic in Dp71. Therefore, Dp71ab is believed to have different roles from Dp71. Previously, we reported that Dp71ab enhanced the proliferation of human myoblasts. Here, we further characterized Dp71ab, focusing on the activation of cell proliferation. Dp71ab increased the proliferation of immortalized human myoblasts in a dose-dependent manner. In contrast, Dp71 suppressed proliferation in a dose-dependent manner. Consistent with these opposite effects, eGFP-tagged Dp71ab and mCherry-tagged Dp71 showed different cellular distributions, with Dp71ab mostly in the nucleus. Notably, human Dp71ab enhanced the proliferation of rat and mouse myoblasts. Despite these findings, human Dp71ab did not enhance the proliferation of human nonmyoblast cells, including rhabdomyosarcoma cells. We concluded that Dp71ab is a myoblast-specific proliferation enhancer. In further studies, Dp71ab will be employed for the expansion of myoblasts in clinical settings.